Kajian Integratif Urgensi Kemitraan Sekolah dalam Menjaga Keberlangsungan Hidup Lembaga Pendidikan Islam - Endah Winarti; Zainal Abidin; Akhmad Fauzi Hamzah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
Previous theoretical and empirical studies have directed partnerships as part of educational activities. However, implementation at the level of Islamic educational institutions is still less than optimum, and studies on the importance of partnerships in Islamic educational institutions are also minimal. In fact, during the current pandemic, partnerships are not the only choice activity for Islamic educational institutions to carry out but are a must for achieving educational goals. For this reason, there is a need to present an integrative literature review on partnerships in the context of Islamic educational institutions that analyzes the crucial reasons for implementing partnerships systematically by Islamic educational institutions. By first discussing what school partnerships are and who is involved in school partnerships, the results of the integrative literature review suggest three crucial reasons why Islamic Education Institutions need to develop partnerships: sustainability, good governance, and quality improvements. The development of school partnerships is urgent and strategic, not only for the sake of realizing the goals of Islamic education but also as an effort to maintain the viability of Islamic education institutions in rapid environmental changes.